2004
DOI: 10.1371/journal.pmed.0010062
|View full text |Cite
|
Sign up to set email alerts
|

Short Sleep Duration Is Associated with Reduced Leptin, Elevated Ghrelin, and Increased Body Mass Index

Abstract: BackgroundSleep duration may be an important regulator of body weight and metabolism. An association between short habitual sleep time and increased body mass index (BMI) has been reported in large population samples. The potential role of metabolic hormones in this association is unknown.Methods and FindingsStudy participants were 1,024 volunteers from the Wisconsin Sleep Cohort Study, a population-based longitudinal study of sleep disorders. Participants underwent nocturnal polysomnography and reported on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

88
1,528
19
93

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,036 publications
(1,791 citation statements)
references
References 40 publications
88
1,528
19
93
Order By: Relevance
“…Elsewhere, in Kenya and the USA, shorter sleep was associated with obesity in women only [47,48]. Evidence suggests that acute short sleep duration results in an imbalance of hormones controlling hunger and appetite, which in turn, are characterized by decreased leptin (satiety hormone), and increased ghrelin (appetite-stimulating hormone) [49,50]. …”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, in Kenya and the USA, shorter sleep was associated with obesity in women only [47,48]. Evidence suggests that acute short sleep duration results in an imbalance of hormones controlling hunger and appetite, which in turn, are characterized by decreased leptin (satiety hormone), and increased ghrelin (appetite-stimulating hormone) [49,50]. …”
Section: Discussionmentioning
confidence: 99%
“…53 Thus, the dramatic increase in the incidence of obesity and type 2 diabetes seems to have developed over the same period of time as the progressive decrease in self-reported sleep duration. [54][55][56] A growing body of epidemiological evidence supports an association between short sleep duration and the risk of obesity [57][58][59][60][61] and type 2 diabetes. [62][63][64][65][66] The potential mechanisms by which sleep deprivation may predispose to obesity are: (1) an alteration of the neuroendocrine control of appetite characterized by a decrease in the levels of the anorexigenic hormone leptin and an increase in the levels of the orexigenic hormone ghrelin; (2) an increased opportunity to eat; (3) an altered thermoregulation; and (4) an increased fatigue leading to reductions in physical activity.…”
Section: Short Sleep Duration: Association With Glucose Homeostasismentioning
confidence: 99%
“…Cross-sectional evidence suggests an association between short sleep and obesity in children [8][9][10][11] and in young adults. [12][13][14][15] In addition, two prospective cohort studies have shown that short sleep predicts future weight gain in young adults 16 and in middle-aged women. 7 The mechanisms linking weight and sleep duration are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A causative path from sleep and circadian clock system to obesity has been suggested through direct metabolic (see for example Kohsaka et al 17 and Kohsaka and Bass 18 ) and/or hormonal changes with an influence on energy intake. 14,19 More indirect pathways are also plausible, for instance, short or disturbed sleep may cause fatigue leading to restriction of physical activity. Physical inactivity may, in turn, have a negative feed-back effect on sleep.…”
Section: Introductionmentioning
confidence: 99%